2006
DOI: 10.4049/jimmunol.177.11.7943
|View full text |Cite
|
Sign up to set email alerts
|

Increased Natural CD4+CD25+ Regulatory T Cells and Their Suppressor Activity Do Not Contribute to Mortality in Murine Polymicrobial Sepsis

Abstract: Regulatory T cells (Tregs), including natural CD4+CD25+ Tregs and inducible IL-10 producing T regulatory type 1 (TR1) cells, maintain tolerance and inhibit autoimmunity. Recently, increased percentages of Tregs have been observed in the blood of septic patients, and ex vivo-activated Tregs were shown to prevent polymicrobial sepsis mortality. Whether endogenous Tregs contribute to sepsis outcome remains unclear. Polymicrobial sepsis, induced by cecal ligation and puncture, caused an increased number of splenic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

16
102
3
2

Year Published

2007
2007
2023
2023

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 119 publications
(123 citation statements)
references
References 41 publications
16
102
3
2
Order By: Relevance
“…Animal studies have documented the requirement of an intact T cell system to adequately combat a septic challenge (29,37). More recently, animal-based experiments have demonstrated that experimental septic shock is characterized by widespread T cell apoptosis and that preventing T cell apoptosis positively impacts the outcome of experimental sepsis (38)(39)(40)(41)(42)(43)(44)(45). Importantly, the concept of T cell apoptosis in human sepsis has been indirectly corroborated by autopsy studies (36,46).…”
Section: R E S E a R C H A R T I C L E M O L M Ementioning
confidence: 74%
“…Animal studies have documented the requirement of an intact T cell system to adequately combat a septic challenge (29,37). More recently, animal-based experiments have demonstrated that experimental septic shock is characterized by widespread T cell apoptosis and that preventing T cell apoptosis positively impacts the outcome of experimental sepsis (38)(39)(40)(41)(42)(43)(44)(45). Importantly, the concept of T cell apoptosis in human sepsis has been indirectly corroborated by autopsy studies (36,46).…”
Section: R E S E a R C H A R T I C L E M O L M Ementioning
confidence: 74%
“…They are increased in percentage in the peripheral blood of sepsis patients compared with that of healthy controls (46), and their number is increased in the spleen of septic mice (47). Whereas their deletion does modify the outcome of septic mice (47), their transfer improved survival in the polymicrobial model of sepsis (48) and contributed to normalize resolution of lung injury in mice exposed to LPS (49). However, they also contribute to the immunosuppressive environment associated with sepsis (50).…”
Section: Discussionmentioning
confidence: 99%
“…The recruitment of innate immune effector cells is important for the containment and control of bacterial infection, as well as abscess formation and localization (7). The characteristics of the adult response to sepsis have been well described but have not been fully delineated in the neonate (6,11,18). Blood, spleen, bone marrow, and peritoneal washes were collected at multiple time points from neonates that were exposed to an LD 40 polymicrobial sepsis.…”
Section: Resultsmentioning
confidence: 99%